BACK MASSAGE MODALITY THERAPY FOR ELDERLY MEMORY CARE (LANGUAGE) IN JEMBER LONG-TERM CARE FACILITY - Kushariyadi Kushariyadi (Faculty of Nursing, Universitas Jember, 2017)
The aging process can reduce the memory in the elderly. Elderly expected memory gets older well maintained so that the function and quality of life of the elderly as a complex and unique individuals to function and prosper. Problem in UPT PSLU Jember is memory loss in the elderly. Elderly expressed concerns about memory loss experienced and perceived long ago. Until now, treatment of memory loss in the elderly in UPT PSLU Jember using nursing a back massage modality therapy has not been given. Type of quasi-experimental research design with one group pre-post test design treatment aimed to compare before treatment group were given nursing intervention modality therapy back massage with after being given intervention. This study aimed to influence nursing a back massage modality therapy in the treatment of memory (language) of the elderly. Sampling techniques used simple random sampling of the elderly in UPT PSLU Jember much as 12 respondents in 2016. The results of the analysis Wilcoxon signed rank test obtained value memory (language) p = 0.034, we conclude there is difference memory (language) of elderly significantly between before and after nursing a back massage modality therapy. Nurses and care giver family jointly provide alternative therapies using the back massage modality therapy for patient care individually and holistically so that elderly to remain productive.